Existence Theorems on Advanced Contractions with Applications. (8th January 2021) - Kim, Sang Og; Nazam, Muhammad
Abstract : In this research article, by introducing a mapping φ defined on 0, ∞ 4, with some axioms, we define two generalized contractions called F H + φ -contractions and φ H P + -contractions. We investigate their mutual relation and establish an existence theorem addressing F H + φ -contractions with some applications.